Cyanobacteria: A green nitrogen for rice - Shahane, Amit A.; Singh, Y. V. (Indian Farming, 2015)
This study shows that cyanobacteria inoculants can be usedto replace approximately one-third (40 kg N/ha) of recommended dose of N fertilizer. Combination of PGPR with BGA and 2/3 dose of chemical N fertilizer gave highest grain yield and net return so this combination can be used in integrated nutrient management of rice. Net returns were also higher in SRI method over conventional method. Since SRI method of rice cultivation saves 34 % of water and increase the water productivity it should be preferred for rice cultivation.